2014
DOI: 10.1016/j.jad.2013.01.054
|View full text |Cite
|
Sign up to set email alerts
|

Blood levels of brain derived neurotrophic factor in women with bipolar disorder and healthy control women

Abstract: Background Brain-derived neurotrophic factor (BDNF) protein has been implicated in the pathophysiology of mood disorders, with early data suggesting that blood levels may vary by severity of mood symptoms. BDNF polymorphism, val66met, has also been implicated in mood disorders. Methods Euthymic women with bipolar disorder (BD) (n=47) and healthy control women (n=26), ages 18–45, were clinically rated using the Montgomery-Asberg Depression Rating Scale (MADRS) and sampled for plasma BDNF concentration, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Blinding of laboratory staff to the clinical state of participants was reported in eight studies. 21,26,46,50,53,56,63,65 One study reported assigning samples randomly through enzyme-linked immunosorbent assay procedures. 26 Risk of bias and study quality within studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blinding of laboratory staff to the clinical state of participants was reported in eight studies. 21,26,46,50,53,56,63,65 One study reported assigning samples randomly through enzyme-linked immunosorbent assay procedures. 26 Risk of bias and study quality within studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…BDNF genotype was investigated in three of the included studies, with two finding no association between the Val66Met BDNF gene single-nucleotide polymorphism and BDNF levels, 40,50 and one study finding lower BDNF levels in bipolar disorder patients carrying the Met allele compared with Val homozygotes. 46 A recent meta-analysis, however, did not find any association between the BDNF Val66Met polymorphism and bipolar disorder.…”
Section: Limitationsmentioning
confidence: 99%
“…Twenty-one case–control association studies met our criteria for the meta-analysis (Table 1 ). Data from four studies [ 26 - 29 ] were excluded due to the partial overlap with a larger sample size case–control study [ 30 ], and data from six studies were excluded due to less than 100 subjects in either patient group or control group [ 31 - 36 ]. Additionally, the case–control sample from a genome-wide association study was also excluded from current meta-analysis [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…174 A recent study comparing BDNF levels in first major depressive episode patients suffering either from bipolar or major depression found that while both groups showed significantly reduced plasma BDNF, those suffering bipolar disorder had even lower BDNF levels than did the major depression patients. 175 However, other studies found either no decrease in plasma BDNF in patients compared with controls 176 or even an increase in plasma BDNF compared with controls. 177 One study found that improvement in symptoms resulting from quetiapine treatment was accompanied by increases in BDNF in patients with depressive episodes and decreases in BDNF in patients with manic or mixed episodes, 178 suggesting differential BDNF alteration according to polarity of disease, adding a layer of complexity in analyzing the role of BDNF.…”
Section: Bdnf and Bipolar Disordermentioning
confidence: 96%